Pengembangan Model Bisnis dan Rantai Nilai Budidaya lebah Apis mellifera.L Skala Kecil dan Menengah di Provinsi Riau - Andhika Silva Yunianto; Avry Pribadi; Hery Kurniawan; Ahmad Junaedi; Siti Wahyuningsih; Michael Daru Enggar Wiratmoko (Faculty of Forestry Universitas Gadjah Mada, 2024)
Beekeeping practice was an alternative livelihood for communities around forest areas, offering a potential solution to reduce conflicts arising from the use and management of this ecosystem. Starting in the COVID-19 pandemic, the government introduced Apis mellifera from Java island into honey production in Sumatra due to its high productivity and adaptability to new environments. Therefore, this research aimed to explore the challenges and develop business models and value chains associated with commercializing Apis mellifera honey. The analysis used a qualitative descriptive method through observation and in-depth interviews with beekeeping entrepreneurs. There were two sales systems. The first was direct from beekeepers, and the second was indirect sales systems facilitated by collectors/industries. The collectors/industries gained a significant profit, approximately IDR. 80,000.00/kg, while beekeepers only received a minimum selling price. Marketing became a significant issue as beekeepers tended to focus more on cultivation efforts, resulting in a simplistic method of honey sales. Consequently, providing maximum economic value to the communities around the forest areas required synergy and assistance from related sectors.